The Role of Communication in The Muslim Community - Sulastri, Sulastri (International Conference of Moslem Society, 2018)
Humans are social beings who need relationships with others by means of communication. Communication can be done orally, in writing, signs, and symbols. It can be done both traditional and modern, with communication tools from simple to sophisticated tools. This is also appied to Muslim community because Islam is a religion of da'wah, ie the religion which obliges its believers to internalize, transmit, diffuse, transform, and actualize Islamic law (syari’ah) with various methods and media sourced from Al-Qur'an, as book of da'wah, and sunnah of Rasulullah to mad'u (mankind). Islamic Communication is aimed at pressenting communication that is able to uphold human values corresponding to the nature of human creation. Islamic Communication is the process of delivering or exchanging information using the principles and in the rules of communication found in the Qur'an and Hadith. Developments in the world of communication has brought us to the global world and make the community continuously use the media so that it needs the creation of information society (information society). Islam never curbs its people to advance and modern. Convesely, Islam strongly supports its people to conduct research and experiment in any case, including communication.